Inpatient dermatological referrals in a tertiary care hospital - Raikar, Dayanand R.; Manthale, Nagendra S.; Raikar, Shrinivas R. (International Journal of Research in Dermatology, 2017)
Background: It is not surprising that patients hospitalized on nondermatology inpatient services are frequently found to have skin problems and present as a source of confusion for their admitting physicians. Aims and Objective: To analyse the reasons for dermatology referrals and its frequency, departments sending the referral and the impact on health care management. Methods: We conducted a study on 464 patient referrals over a 4‑year period. The demographic details, specialties requesting consultation, cause of referral, and dermatological advice have been recorded and analyzed. Results: Unspecified “skin rash” was the most common dermatologic condition for which skin referral was sought. The final diagnoses made by dermatologists revealed infections as most common skin disorder. Almost 48% of the patients referred as “skin rash” were diagnosed to be suffering from infectious disorders. The referring doctors could provide an accurate dermatological diagnosis only in 32% of cases. Conclusions: Most of the nondermatologists fail to diagnose common skin disorders. This reveals need for more trained dermatologists to combat this problem and more extensive dermatological training for the medical students.